1992
DOI: 10.1007/bf01967063
|View full text |Cite
|
Sign up to set email alerts
|

Cotrimoxazole therapy ofToxoplasma gondii encephalitis in AIDS patients

Abstract: Twenty-four consecutive HIV-positive patients affected by Toxoplasma gondii encephalitis received trimethoprim-sulfamethoxazole (cotrimoxazole) as acute-phase treatment. Two dosage regimens of cotrimoxazole were used: 40 mg/kg/day (12 patients) or 120 mg/kg/day (12 patients) of total compound (trimethoprim plus sulfamethoxazole). Clinical and radiological responses to treatment were evaluated, and the product-limit method for survival data analysis was used. Eighteen of 24 patients showed both a clinical and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 20 publications
1
21
0
2
Order By: Relevance
“…This standard combination has been successfully used in treating CT but has been associated with high toxicities such as Lyell's syndrome or Steven-Johnson syndrome (Katlama et al, 1996a;Torre et al, 1998). The other regimen is trimethoprim/sulfamethoxazole (Co-trimoxazole, 5/25 mg/kg PO or intravenous (IV) every 12 h for 4-6 weeks) (Canessa et al, 1992). This therapeutic regimen has been confirmed for its efficacy and safety in a single available randomized clinical trial (Canessa et al, 1992;Torre et al, 1998;Dedicoat & Livesley, 2006;Béraud et al, 2009).…”
Section: Anti-toxoplasma Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…This standard combination has been successfully used in treating CT but has been associated with high toxicities such as Lyell's syndrome or Steven-Johnson syndrome (Katlama et al, 1996a;Torre et al, 1998). The other regimen is trimethoprim/sulfamethoxazole (Co-trimoxazole, 5/25 mg/kg PO or intravenous (IV) every 12 h for 4-6 weeks) (Canessa et al, 1992). This therapeutic regimen has been confirmed for its efficacy and safety in a single available randomized clinical trial (Canessa et al, 1992;Torre et al, 1998;Dedicoat & Livesley, 2006;Béraud et al, 2009).…”
Section: Anti-toxoplasma Therapymentioning
confidence: 99%
“…The other regimen is trimethoprim/sulfamethoxazole (Co-trimoxazole, 5/25 mg/kg PO or intravenous (IV) every 12 h for 4-6 weeks) (Canessa et al, 1992). This therapeutic regimen has been confirmed for its efficacy and safety in a single available randomized clinical trial (Canessa et al, 1992;Torre et al, 1998;Dedicoat & Livesley, 2006;Béraud et al, 2009). Several alternative therapies, principally used in patients who are intolerant to this combination, have been reported to be effective, including clindamycin and pyrimethamine or sulfadiazine (Katlama et al, 1996a;Tsai et al, 2002), clarithromycin and pyrimethamine (Fernandez-Martin et al, 1991), clindamycin and 5-fluoro-uracil (Dhiver et al, 1993), azithromycin and pyrimethamine (Saba et al, 1993;Jacobson et al, 2001), clindamycin and fansidar (Nissapatorn et al, 2004), sulfadoxine and pyrimethamine (Amogne et al, 2006), and atovaquone (Torres et al, 1997).…”
Section: Anti-toxoplasma Therapymentioning
confidence: 99%
“…One small case series reported by Canessa et al demonstrated effectivity of co-trimoxazole alone. 8 The evidence for effectiveness of this regime in severe disease is limited. These regimens have been recommended when standard therapy not tolerated.…”
Section: Discussionmentioning
confidence: 99%
“…En estos enfermos se recomienda mantener el tratamiento con el fármaco que se ha usado en la fase aguda: pirimetamina sola o asociada a atovaquona, azitromicina, minociclina o doxicilina, 5-fluorouracilo y clindamicina, y minociclina o doxicilina con sulfadiazina. Igualmente existe muy poca experiencia con dapsona y pirimetamina o con cotrimoxazol 123,[125][126][127][128][129][130][131][132][133][134][135][136][137][138][139][140][141][142] (CII). También se ha utilizado claritromicina (1 g/12 h) en lugar de azitromicina, pero no se recomienda dado que la claritromicina a esas dosis se asociara a un exceso de mortalidad en un estudio de profilaxis frente al MAC 143 .…”
Section: Profilaxis Secundariaunclassified